The Effect of Job Satisfaction, Person-job fit and Servant Leadership on Employee Performance - Saputra, Bintang Adi; Kurniawan, Ignatius Soni; Isyander, Mohammad Ahyar Syafwan (Universitas Pamulang, 2025)
This study aims to analyze the effect of job satisfaction, person-job fit, and servant leadership on employee performance at the Yogyakarta City Fire and Rescue Service. This research uses a quantitative approach with a saturated sampling method, involving the entire population of 40 respondents. Primary data was collected through a Likert scale-based questionnaire and analyzed using multiple linear regression method with SPSS software. The results showed that job satisfaction has a significant influence on employee performance, while person-job fit and servant leadership do not have a significant influence. This finding indicates that improved employee performance in this organization is influenced by the level of job satisfaction, which is indicated by the highest rating on the aspect of overall satisfaction with work. Meanwhile, although person-job fit and servant leadership were rated positively by respondents, these variables have not contributed significantly to performance improvement. These results imply the need to focus on improving job satisfaction through strategies such as providing appreciation, recognizing achievements, and improving the comfort of the work environment. In addition, this study recommends exploring other factors such as work motivation, organizational support, and person-organization fit that may have a greater influence on employee performance. This study provides practical implications for organizational leaders in developing more comprehensive and holistic policies to improve the effectiveness of employee performance. Further research is expected to expand population coverage by involving similar agencies in other regions and adding new relevant variables to provide a deeper understanding of the factors that influence employee performance in the public sector.